'Into the Unknown': a Comparative Study of Figurative Language in German, Tamil, and English - Sivan, Pavita; Jalis, Farhana Muslim Mohd (Nexus Publishing, 2024)
Figurative language is vocabulary that is used creatively, departing from its literal meaning. Song is one of the resources used by language learners to fill in the gaps between one another. This study was done for non-native speakers of foreign languages who might have trouble understanding figurative language. Finding the most common figurative language among the three languages is the goal of this study. Perrine's theory is applied in this study to analyze the kind of figurative language. Furthermore, Tilly's theory was applied to analyze the figurative language's contextual meaning. The types of figurative language were analyzed in this study using a qualitative method. There are 37 types of figurative language from the English version, 22 types from the Tamil version, and 29 types from the German version. The English version is the most frequently used figurative language among the three languages. Therefore, researchers in the future should examine the parallels, differences, and trends in these languages' use of figurative language, according to this study.